Association between anogenital distance as a noninvasive index in the diagnosis and prognosis of reproductive disorder: A systematic review - Parisa Zamani; Zeinab Hemati; Roya Kelishadi; Sakineh Kolahdozan; Mostafa Dianatinasab; Mojtaba Keikha (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: There are 2 measures of anogenital distance (AGD) in men and women. AGD has been used as an indicator of fetal androgen dysfunction and an adverse outcome in adulthood. Some studies have shown the association of AGD as a predictor in the diagnosis and prognosis of diseases and disorders. Objective: To systematically summarize the latest evidence for presenting AGD as a new approach for prognosis and early diagnosis of diseases. Materials and Methods: A systematic review of the available literature was performed using Medline via PubMed, Scopus, and ISI Web of Knowledge up to July 2021, using search terms "anogenital distance" OR "anogenital index" OR "ano genital distance" OR "ano genital index". Language restrictions were not imposed. Results: After reviewing the retrieved articles, 47 unique studies were included in this systematic review. Different outcomes, including endometriosis, prostate cancer, polycystic ovary syndrome, pelvic organ prolapse, hypospadias, cryptorchidism, fertility and semen parameters, maternal and birth development, and ovarian and gynecological-related disorders, have been studied in the included evidence. A negative association was observed between AGD and endometriosis and hypospadias and a positive association between AGD and prostate cancer, polycystic ovary syndrome, male fetal gender, and fertility parameters. Conclusion: Using quantitative indicators such as AGD may be a useful clinical tool for the diagnosis of diseases. Although many studies have shown an association between AGD and diseases, some factors, including different measurement methods, different measurement tools, age, and different definitions of AGD, can be involved in the variation of AGD.Key words: Genitalia, Prognosis, Early diagnosis, Reproductive health.